(untitled) (Revista Logos Ciencia & Tecnología, 2019)
Objective: To characterize the articulation of milk producers in Córdoba, Colombia. Methods: Descriptive multicast study composed of 11 producers and a dairy cooperative. Surveys and an interview were applied, the information was analyzed using descriptive statistics and content analysis. Results: The dairy cooperative within the production chain performs: milk collection (70% comes from associates), processing and marketing. The purchase criterion is to deliver the milk at low temperature to minimize risks. This contributes to the producer in receiving a benefit in the price of the product. Most dairy farms are medium-sized; they produce milk on average of 4.8 L/cow/day, whose price received in the market varies from US 0.32 / L to US 0.47 / L. Vertical articulation is carried out between producers, processing companies and the cooperative where they receive support in technical and financial assistance; horizontal articulation based on alliances between producers to collect milk in cold tank. Conclusions: There are few producers associated with a cooperative for a better articulation within the value chain, although more than half commercialize milk in formal markets prevents them from enjoying the benefits of being in a solidarity organization.